Methodological perspectives of Physical Education - Cereda, Ferdinando (Formazione & insegnamento, 2017)
The methodology of physical activities are taken into account and are situated in the contemporary educational horizon. Its importance in the educational acting on both the body and the mind is described in the general educational context and in the school context as well. Physical education has its primary scope in developing all the functions of the person considered in all the components that constitutes the selfsame person. Physical education has its reason of existing in methodological and teaching models that make possible the introduction to sport education and to actual sport. The goals of physical education have to be included in those of the general education and a methodological discourse has to be based upon these premises, that is what is to be effected by means of movement and basing upon this choosing the means considered more suitable to fulfil them.